Efforts to Improve Dribbling Learning Outcomes in Basketball Games Through a Scientific Approach With Ball Modifications - Aini Pasaribu (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2022)
This research is a classroom action research (Classroom Action Research) with the stages of implementation include planning, implementing action, observation, and reflection. The location of this research was carried out in class VIII of Muhammadiyah 27 Private Junior High School. After the data was collected an analysis would be carried out: From the test of learning outcomes before using the scientific approach (pre-test) obtained 9 students (29.03%) who had achieved mastery learning, while 22 students ( 70.69%) have not reached the level of complete learning. With an average value of 58.33. Then learning is carried out using a scientific approach in cycle I. From the test of learning outcomes in Cycle I dribbling through a scientific approach in cycle 1, 19 students (61.29%) have reached the level of mastery learning, while 12 students (38.70%) have not. achieve the level of mastery learning. With an average value of 69.73. Then the dribbling learning was carried out again with a scientific approach. From the learning outcomes test conducted in the second cycle, 27 students (87.09%) achieved the mastery level of learning, while 4 students (12.90%) had not yet reached the mastery level in learning, with an average score of 81.66. In this case, it can be seen that there is an increase in the average value of learning outcomes in cycle I and cycle II, namely 11.93. Based on the results of data analysis, it can be said that through a scientific approach it can improve basketball dribbling learning outcomes for class VIII students of Muhammadiyah Private Junior High School 27, West Sorkam District, Middle Tapanuli Regency for the 2020/2021 Academic Year.